Analysis of a direct vapor generation system using cascade steam-organic Rankine cycle and two-tank oil storage. (15th October 2022) - Li, Pengcheng; Lin, Haiwei; Li, Jing; Cao, Qing; Wang, Yandong; Pei, Gang; Jie, Desuan; Zhao, Zilong
Abstract: A direct vapor generation solar power system using cascade steam-organic Rankine cycle and two-stage oil tanks is proposed. It offers a significantly enlarged storage capacity due to the unique discharge operation mode. Synthetic oil Therminol® VP-1 is used as the heat carrier and storage medium. Compared with the direct steam generation system, the steam turbine inlet temperature is elevated from 270 °C to 311 °C. Thermodynamic analysis indicates that the optimal equivalent heat-to-power conversion efficiency ( η e q, o p t ) is 27.91% when benzene is used as the bottom fluid and the mass of oil is 1000 tonnes. η e q, o p t is raised by 7.72–11.60% for the selected four organic fluids as compared with the direct steam generation type. The temperature drop of oil during discharge can reach about 280 °C. Economic studies demonstrate that the proposed system is more cost-effective. Its equivalent payback period is less than 5 years for a 10 MW system with 2000 tonnes of oil. Further investigation shows that it is also more advantageous than a conventional thermal oil-based indirect solar power system due to the cost reduction in heat storage. Highlights: Thermal oil is innovatively combined with a cascade steam-organic Rankine cycle. Challenges associated with high-pressure steam generation are overcome. An efficiency of 30.25% is obtained at a solar field temperature of 311 °C. The temperature drop of thermal oil during discharge is significantly elevated. The equivalent payback period is generally less than 7.5 years.